2016
DOI: 10.1016/j.meegid.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of HTLV-1 sequences suggest interaction between ORF-I mutations and HAM/TSP outcome

Abstract: The region known as pX in the 3′ end of the human T-cell lymphotropic virus type 1 (HTLV-1) genome contains four overlapping open reading frames (ORF) that encode regulatory proteins. HTLV-1 ORF-I produces the protein p12 and its cleavage product p8. The functions of these proteins have been linked to immune evasion and viral infectivity and persistence. It is known that the HTLV-1 infection does not necessarily imply the development of pathological processes and here we evaluated whether natural mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
(47 reference statements)
0
14
0
1
Order By: Relevance
“…Many PTLV-1 strains (Table C in S1 Text) were analyzed and the presence of P12, P13 et P30 were addressed, focusing mostly on the conservation of the splicing sites, the presence of the start codon and the absence of early stop codon (Tables D-F in S1 Text). * although the complete sequences of HTLV-1a all encode a 99 aa-long protein, many shorter versions of the proteins have been reported [16, 17]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many PTLV-1 strains (Table C in S1 Text) were analyzed and the presence of P12, P13 et P30 were addressed, focusing mostly on the conservation of the splicing sites, the presence of the start codon and the absence of early stop codon (Tables D-F in S1 Text). * although the complete sequences of HTLV-1a all encode a 99 aa-long protein, many shorter versions of the proteins have been reported [16, 17]. …”
Section: Resultsmentioning
confidence: 99%
“…* although the complete sequences of HTLV-1a all encode a 99 aa-long protein, many shorter versions of the proteins have been reported [16, 17]. …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the authors found that the pattern of p12 and p8 expression correlated with proviral load [58]. In a second study using a computational approach to examine p12/p8 sequence variants (D26N, G29S, P34L, L40F, P45L, S63P, L66P, S69G, R83C) in healthy carriers of HTLV-1 and HAM/TSP patients, P45L, S69G, and R88K were found more frequently in patients positive for HAM/TSP, and D26N, P34L, C39R, F61L, and R83C were found to be associated with low proviral load [59].…”
Section: Htlv-1a Orf-imentioning
confidence: 99%
“…This study did not exclude the possibility that orf - I could be expressed by an alternative doubly spliced mRNA in these patients (Table 1). It is important to note that studies that examine the p12 sequence from patient PBMCs in vivo have relied on PCR amplification and cloning of viral DNA regions, resulting in amplification of the most dominant clones [58, 59, 141] that may not be infectious. Therefore, it is possible that where premature termination of p12 was found, minor intact clones are also present that contribute to infection and/or viral persistence.…”
Section: Htlv-1a Orf-imentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] Previous studies demonstrated that mutations in p12 may influence the HTLV-1 infection outcome. 3,5,8,16,17 Here, we identified, at the first time, a HTLV-1 strain with a premature stop codon in p12 infecting an individual from Brazil, presenting a very low proviral load. We hypothesize if this mutation would have a protective role against HTLV-1 replication.…”
mentioning
confidence: 92%